Theorizing ICT-based social innovation on development in the context of developing countries of Africa - Ngonzi, Tibuhinda T (Department of Information Systems, 2016)
Background - The main concern of this study is that the perspectives at the foundation of the deployment of information and communication technologies (ICT) undermine the pertinent long-term benefits in developing countries. Not only that, but they also affect the ways in which communities in the global information society engage themselves in the diffusion process of ICT. Claim of the study - The innovation and diffusion process of ICT in developing countries of Africa is foreign and sponsor driven. Consequently, the process is infested with a focus on the realizations in the short-term, with a continued domination of technological innovations by the technologically advanced communities. The argument in this study is that Africa's developing countries need to change their perspectives, and play an active role to drive the diffusion process of ICT in local contexts for long-term developmental impacts. Purpose of the study - The main aim of this study is to explore the conceptions surrounding ICT processes in theory and practice, for the purpose of gaining insight into the improved approaches for applied ICT. The study looks into ways through which local communities and their governments in Africa's developing countries can play a role in cultivating the enhancement of ICT to promote productivity, like it has happened in other places of the world. Problem statement - The assumption for the problem statement draws from the expressed main concern in the background. That is, there is a need for adequate theoretical foundations to appropriately guide the ICT deployment and application initiatives for effective social development in Africa's DCs. In the other words, theoretical contributions in the discipline of information systems are needed to explain the relationships between long-term impacts of ICT and societies, and the frameworks for practice to realize the impacts.